Limitations of protein-coated charcoal in the separation of free from bound vitamin B12 in serum. Issue 9 (September 1983) - Jacob, E; Wong, K T
Abstract : The effect of haemoglobin and albumin-coated charcoal on the concentration of vitamin B12 binding proteins in serum has been investigated. As commonly employed, coated charcoal removes a significant amount of transcobalamin II (TCII) from serum, but does not affect transcobalamin I and III (TCI and III). Increasing the protein coat up to about 10 mg of protein per 25 mg of charcoal reduces the adsorption of TCII, but increasing the protein concentration beyond this has little added effect. The amount of adsorption is proportional to the amount of coated charcoal employed, but even small amounts adsorb some TCII. These results indicate that protein-coated charcoal is not the ideal way of separating free from bound vitamin B12 in serum; it cannot reliably be used for the measurement of the concentration of apo-TCII but can be employed for the measurement of apo-TCI and III.